Dataset: Sharing the seas: A review and analysis of ocean sector interactions - Crona, Beatrice; Wassénius, Emmy; Lillepold, Kate (Stockholm University, 2020)
Ocean activities are rapidly expanding, but there is little understanding of their interactions. We review >3000 articles to analyze ocean sector interactions and find >90 unique direct and >150 indirect interactions often mediated via the ocean ecosystem. All interactions outcomes were categorized and reveal that some sectors coexist synergistically, but many interactions are antagonistic, including a significant amount of environmental impacts. In a related paper, we use this analysis to propose principles that can guide strategic decision-making, help navigate tradeoffs, and identify opportunities for sustainable and equitable governance trajectories. This dataset has four main components; a) A detailed account of our systematic mapping of peer-reviewed literature; b) Detailed summaries of the ocean interactions yielded from our analysis; c) All articles retrieved by our systematic search and subsequent literature review; d) All ocean interactions yielded from the review, categorized into outcome types. Accompanying R scripts can be found at: https://github.com/klillepold/OceanInteractions
Keywords: Earth and Environmental Sciences; Other; sustainability; blue economy; ocean governance; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap